2015
DOI: 10.5539/jas.v7n9p160
|View full text |Cite
|
Sign up to set email alerts
|

Resource Use Efficiency of Tea Production in Vietnam: Using Translog SFA Model

Abstract: As one of the most important economic activities to small households of Vietnam, tea production is hindered by low productivity, rising of production costs, and bad agriculture practices. To sustain tea production, the near-term strategy is to improve the efficiency of resource utilization. To our knowledge, this article is the first study to evaluate the tea production's resource use efficiency and to identify the factors affecting it in Vietnam. The data was collected from 243 randomly selected tea farmers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 20 publications
(26 reference statements)
0
24
2
1
Order By: Relevance
“…called input-oriented TE "IO" [13,16]. There are some basic differences between the OO and IO models as features of the technology are concerned, see further details in [13] and [18]. Furthermore, TE in production is defined as the ability of the producer (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…called input-oriented TE "IO" [13,16]. There are some basic differences between the OO and IO models as features of the technology are concerned, see further details in [13] and [18]. Furthermore, TE in production is defined as the ability of the producer (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, agricultural extension services play a crucial role in training technology, improving income, and reducing poverty for locals in rural areas of Vietnam [50,51]. Moreover, the positive coefficient of the experience EE confirmed that farmers with more years in edible canna cultivation can achieve higher efficiency level compared to less experienced counterparts, which is in line with Hong and Yabe [14].…”
Section: Factors Influencing On Environmental Efficiency Of Edible Camentioning
confidence: 75%
“…β ij LnX i (14) where i represents the number of input variables and j presents the number of explanatory variables. For example, the output elasticity of seed input (X 1 ) is can be calculated as:…”
Section: The Output Elasticity For Each Inputmentioning
confidence: 99%
See 1 more Smart Citation
“…Elsewhere, farm level technical efficiency and determinants of tea production have been studied in Vietnam (Hong & Yabe 2015a). Results showed that the tea farmers were technically inefficient.…”
Section: Introductionmentioning
confidence: 99%